(untitled) (Bangladesh Journal of Agricultural Research, 2023)
The presence of plant-parasitic nematodes causing crop loss every year had been overlooked in the existing fruits, vegetables and flowers cultivation system in Bangladesh. Therefore, the study was conducted to isolate and identify plantparasitic nematodes from soil and infected plant-parts of fruits (banana, orange), vegetables (pointed gourd, tomato and brinjal) and flower (gerbera) from the districts of Jashore, Jhenaidah, Gazipur and Sylhet during 2017-18 and 2018-19 cropping seasons. A total of 68 samples of which 20 fruit samples, 45 vegetables samples and 3 flower samples were collected and observed for nematode infestation. Baermann funnel method was used to extract the active nematodes from plant parts and Cobb’s method was used for the isolation of nematodes from soil samples. Different morphological structures of the nematodes viz. esophagus, median bulb, basal bulb, intestine, reproductive structures (vulba, bursa), etc. were used to identify the nematodes. To identify Meloidogyne spp. from root knot of tomato, brinjal and gerbera, juvenile larvae J2 and perineal pattern of female nematodes were used. A total of six genera of nematodes were identified and all of them were under the order Tylenchida. The nematode genera were Tylenchorhynchus sp., Tylenchus sp., Hoplolaimus sp., Helicotylenchus sp., Pratylenchus sp. and Meloidogyne spp. The root-knot nematode, Meloidogyne incognita was recorded for the first time in flower crop gerbera in Bangladesh. Bangladesh J. Agril. Res. 46(3): 275-284, September 2021